Sodium-ion battery positive electrode material as well as preparation method and application thereof
By using Te6+ doping and metal selenium compound coating, the structural instability of sodium-ion battery layered oxide materials was solved, thereby improving the rate performance and cycle performance of the cathode material.
Patent Information
- Application Number
- CN202411353075.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
AI Technical Summary
Existing sodium-electric layered oxide materials suffer from excessive lattice oxygen oxidation, leading to microstructure deterioration, poor redox reversibility, and low rate performance and cycle performance.
By employing high-valence element Te6+ doping and metal selenium compound coating, and then treating the material with a second calcination in an oxygen-containing atmosphere or an inert gas atmosphere, strong Te-O covalent bonds and a dense passivation layer are formed, stabilizing the crystal structure and improving the structural and interfacial stability of the material.
It enhances the structural stability and redox reversibility of the material, improves rate performance and cycle performance, and reduces structural damage caused by oxygen release.
Smart Images

Figure CN119284843A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have been considered a sustainable solution to alleviate the resource anxiety of lithium-based electrochemical energy storage, mainly from abundant and low-cost sodium raw materials. In recent years, the development of stable layered cathode and carbon anode materials has been widely reported. However, compared with Li, Na is heavier and has a smaller reduction potential, and the practical application of sodium-ion batteries faces the problem of low specific energy. Specifically, the cost per kilowatt-hour of sodium-ion batteries should be reduced to improve their market competitiveness with lithium batteries. To achieve this goal, a feasible strategy is to increase the specific energy and energy density on a single cell. For the positive electrode active material therein, the positive electrode active material is required to work reversibly at high voltage and have a large amount of Na + Layered oxide cathodes as positive electrode active materials with anionic redox reactions occurring during high-voltage deoxygenation offer a route to achieving high-energy-density sodium-ion batteries because it provides additional capacity by storing charges on transition metal cations and oxygen anions.
[0003] Although the development of sodium-based layered oxide materials with anionic redox reactions is an effective way to increase capacity, the reversibility of redox is still a huge challenge. Existing sodium-based layered oxide materials still have excessive lattice oxygen oxidation, which produces irreversible oxygen release and affects transition metals, deteriorating their microstructure and reducing the reversibility of redox, resulting in low rate performance and cycle performance of sodium-based layered oxide materials. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing sodium-ion battery layered oxide materials still have excessive lattice oxygen oxidation, which deteriorates their microstructure and reduces the reversibility of redox, thus leading to low rate performance and cycle performance of the sodium-ion battery layered oxide materials, thereby providing a sodium-ion battery positive electrode material and its preparation method and application.
[0005] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0006] 1) mixing a sodium source, a precursor and a hexavalent tellurium source, and performing a first calcination to obtain a sintered material;
[0007] 2) The calcined material obtained in step 1), the metal selenium compound and the organic solvent are mixed, and subjected to a second calcination to obtain the sodium ion battery positive electrode material.
[0008] Preferably, in step 2), the second calcination is carried out in an oxygen-containing atmosphere;
[0009] Optionally, the second calcination is performed under an oxygen atmosphere.
[0010] Preferably, in step 2), the second calcination is carried out under an inert gas atmosphere;
[0011] Optionally, the second calcination is performed under a nitrogen atmosphere.
[0012] Preferably, the precursor in step 1) comprises a nickel-iron-manganese precursor;
[0013] Optionally, the chemical formula of the nickel-iron-manganese precursor is Ni x Fe y Mn z (OH) 2 , and x+y+z=1, 0.1≤x≤0.8, 0.1≤y≤0.8, 0.1≤z≤0.8;
[0014] The sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, and sodium oxalate;
[0015] The hexavalent tellurium source is selected from tellurium trioxide.
[0016] Preferably, in step 1), the ratio of the molar amount of the sodium element in the sodium source, the total molar amount of the metal elements in the precursor, and the molar amount of the tellurium element in the hexavalent tellurium source is 0.70: (0.95-0.99): (0.01-0.05);
[0017] The total molar amount of the metal elements in the precursor of the present invention is the sum of the molar amounts of the individual metal elements in the precursor. For example, it is understandable that the nickel iron manganese precursor Ni x Fe y Mn z (OH) 2 The total molar amount of metal elements in is the sum of the molar amount of nickel element, the molar amount of iron element and the molar amount of manganese element.
[0018] In step 1), the first calcination temperature is 900-1000° C. and the first calcination time is 10-24 hours;
[0019] Optionally, in step 1), the first calcination atmosphere is an air atmosphere;
[0020] Optionally, the first calcination further includes cooling and crushing steps.
[0021] Optionally, the heating rate of the first calcination is 1-10°C / min.
[0022] Preferably, the metal selenium compound in step 2) is selected from NiSe, Cu 2 Se, CaSe, Fe 2 Se 3 、Co 2 Se 3 、Al 2 Se 3 、TiSe、SnSe 2 , Sb 2 Se 3 At least one of:
[0023] The organic solvent is selected from at least one of ethylene glycol methanol, ethanol, isopropanol, ethyl ether, acetone and ethyl acetate.
[0024] Preferably, the mass ratio of the sintered material to the selenium element in the metal selenium compound in step 2) is 100:(0.1-2.0);
[0025] In the mixed solution formed by mixing the first sinter, the metal selenium compound and the organic solvent, the total mass concentration of the first sinter and the metal selenium compound is 20-50%;
[0026] The sintered material, the metal selenium compound and the organic solvent are mixed by grinding.
[0027] Preferably, in step 2), the second calcination temperature is 450-850° C., and the second calcination time is 5-10 h;
[0028] Optionally, the second calcination further includes cooling and screening steps.
[0029] Optionally, the second calcination step further includes a drying step.
[0030] The present invention provides a sodium ion battery positive electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery positive electrode material.
[0031] The present invention also provides a sodium ion battery, which comprises the sodium ion battery positive electrode material described above.
[0032] The technical solution of the present invention has the following advantages:
[0033] (1) The preparation method of the positive electrode material of a sodium ion battery provided by the present invention comprises the following steps: 1) mixing a sodium source, a precursor and a hexavalent tellurium source, and performing a first calcination to obtain a sintered material; 2) mixing the sintered material obtained in step 1), a metal selenium compound and an organic solvent, and performing a second calcination to obtain the positive electrode material of a sodium ion battery. 6+By doping and replacing some transition metal ions, a strong Te-O covalent bond was successfully introduced, which stabilized the lattice structure, inhibited the phase transition under high voltage, reduced the microcracks caused by anisotropic volume change, thereby inhibiting the mechanical degradation of the particles and improving the structural stability of the material during the charge and discharge process. 6+ The introduction of Te can reduce the average valence of nickel ions in the material, thereby enhancing the redox activity of the cations. 6+ Doping can refine the primary particles and make them radially arranged, providing good Na + The diffusion channel and the enlarged interlayer spacing increase the diffusion rate of Na+ and enhance the rate performance of the material; at the same time, the metal selenium compound is coated during the second calcination to form a dense / coating on the surface of the particles, which effectively improves the electrochemical stability of the material. And part of the Se element is doped into the surface of the particles, selectively adsorbed in the oxygen vacancies to form a stable O-TM-Se bond, effectively stabilizing the lattice oxygen and preventing structural distortion; this application is doped with high-valent element Te 6+ Coating of metal selenium compounds - a trinity modification strategy for microstructure regulation, high-valent element Te 6+ Doping and metal selenium compound coating work synergistically to enhance the effects of each component and effectively enhance the structure and interface stability of the material. The resulting sodium ion battery positive electrode material has a stable structure, a stable interface, good redox reversibility, and good rate performance and cycle performance.
[0034] (2) In the method for preparing the positive electrode material for a sodium ion battery provided by the present invention, the second calcination in step 2) is carried out in an oxygen-containing atmosphere; optionally, the second calcination is carried out in an oxygen atmosphere. In an oxygen-containing atmosphere, the metal selenium compound will completely react to generate metal oxide and selenium oxide coated on the surface of the material, which is equivalent to coating the metal oxide and SeO on the particle surface at the same time. 2 , SeO 2 As a low melting point compound, it is in a molten state at high temperature and forms a dense coating layer on the surface of the particles, which reduces hydrofluoric acid corrosion and is beneficial to improving the interface stability of the material.
[0035] (3) In the preparation method of the positive electrode material for sodium ion batteries provided by the present invention, the second calcination in step 2) is carried out in an inert gas atmosphere; optionally, the second calcination is carried out in a nitrogen atmosphere. The metal selenium compound is coated in an inert gas atmosphere, and the obtained metal selenium compound coating layer is stable under anaerobic conditions, and reacts with the released active oxygen during high-voltage charging to form a metal oxide and selenium oxide passivation layer, thereby promoting in-situ coating on the surface of the primary particles and the interface of the internal primary particles, forming a dense passivation layer, which will further inhibit the penetration and loss of oxygen through the coating from a kinetic point of view, can reduce hydrofluoric acid corrosion, provide electrostatic shielding, improve the interface stability of the material, and reduce the effect of structural damage caused by oxygen release.
[0036] (4) The method for preparing the positive electrode material of a sodium ion battery provided by the present invention, wherein the metal selenium compound in step 2) is selected from NiSe, Cu 2 Se, CaSe, Fe 2 Se 3 、Co 2 Se 3 、Al 2 Se 3 、TiSe、SnSe 2 , Sb 2 Se 3 The present invention uses specific metal selenium compounds for coating. These specific metal selenium compounds are stable under anaerobic conditions and are easily oxidized into metal oxides and selenium oxides by oxygen in the air. For example, Cu 2 Se is easily oxidized to CuO and SeO by oxygen in the air 2 , after coating in an oxygen-containing environment, CuO and SeO are formed 2 Coating layer; when it is coated in an inactive atmosphere, Cu 2 Se exists stably, Cu 2 Se as a coating layer has three-dimensional Na+ diffusion channels and excellent conductivity, which accelerates the diffusion of Na+ and also partially blocks the Cu+ 2 Se reacts with the released active oxygen to form CuO and SeO at the interface 2 The product forms a dense passivation layer, which will further inhibit the penetration and loss of oxygen through the coating from a kinetic perspective, reduce the structural damage caused by oxygen release, and improve the stability of the structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 SEM image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0041] Example 1
[0042] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0043] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0044] 2) The sintered material obtained in step 1) and Cu 2 Se metal selenium compound and ethylene glycol organic solvent are mixed in a high energy ball mill to form a mixture. 2 The total mass concentration of Se is 40%, the sintered material and Cu 2The mass ratio of Se element in Se is 100:0.4, and then the mixture is dried at 85° C. in vacuum, and then calcined at 600° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0045] Example 2
[0046] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0047] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0048] 2) The sintered material obtained in step 1) and Cu 2 Se metal selenium compound and ethylene glycol organic solvent are mixed in a high energy ball mill to form a mixture. 2 The total mass concentration of Se is 40%, the sintered material and Cu 2 The mass ratio of Se element in Se is 100:0.3, and then the mixture is dried at 85° C. in vacuum, and then calcined at 550° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0049] Example 3
[0050] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0051] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.97:0.03, and the uniformly mixed materials are calcined at a temperature of 950° C. at a heating rate of 2° C. / min in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0052] 2) The sintered material obtained in step 1) and Cu2 Se metal selenium compound and ethylene glycol organic solvent are mixed in a high energy ball mill to form a mixture. 2 The total mass concentration of Se is 40%, the sintered material and Cu 2 The mass ratio of Se element in Se is 100:0.3, and then the mixture is dried at 85° C. in vacuum, and then calcined at 600° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0053] Example 4
[0054] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0055] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0056] 2) The sintered material obtained in step 1) and Cu 2 Se metal selenium compound and ethylene glycol organic solvent are mixed in a high energy ball mill to form a mixture. 2 The total mass concentration of Se is 40%, the sintered material and Cu 2 The mass ratio of Se element in Se is 100:0.4, and then the mixture is dried at 85° C. in vacuum, and then calcined at 600° C. for 6 hours in an air atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0057] Example 5
[0058] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0059] 1) NaOH, Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined in a box furnace at a heating rate of 5°C / min to 900°C in an air atmosphere for 24 hours, and then cooled and crushed to obtain a burnt material;
[0060] 2) The sintered material obtained in step 1) and SnSe 2 The metal selenium compound and ethylene glycol organic solvent are mixed evenly in a high-energy ball mill to form a mixture, wherein the mixture contains a sinter and SnSe 2 The total mass concentration is 50%, a sinter and SnSe 2 The mass ratio of Se element in the mixture is 100:0.1, and then the mixture is dried at 85° C. in vacuum, and then calcined at 450° C. for 10 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0061] Example 6
[0062] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0063] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are uniformly mixed in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined in a box furnace at a heating rate of 2°C / min to 1000°C for 12 hours under air atmosphere, and then cooled and crushed to obtain a burnt material;
[0064] 2) The sintered material obtained in step 1), the NiSe metal selenium compound and the ethylene glycol organic solvent are uniformly mixed in a high-energy ball mill to form a mixture, wherein the total mass concentration of the sintered material and NiSe in the mixture is 20%, and the mass ratio of the Se element in the sintered material and NiSe is 100:2, and then the mixture is vacuum dried at 85° C., and then calcined at 850° C. for 5 h in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0065] Comparative Example 1
[0066] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0067] 1) Na 2 CO 3 、Ni 0.2 Fe0.3 Mn 0.5 (OH) 2 Precursor, TiO 2 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the titanium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0068] 2) The sintered material obtained in step 1) and TiO 2 and ethylene glycol organic solvent are mixed evenly in a high energy ball mill to form a mixture, wherein the sintered material and TiO 2 The total mass concentration of the sintered material and TiO is 40%. 2 The mass ratio of the Ti element in the mixture is 100:0.4, and then the mixture is dried at 85° C. in a vacuum oven, and then calcined at 600° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0069] Comparative Example 2
[0070] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0071] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TiO 2 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the titanium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0072] 2) The sintered material obtained in step 1) and Cu 2 Se and ethylene glycol organic solvent are mixed evenly in a high energy ball mill to form a mixture. 2 The total mass concentration of Se is 40%, the sintered material and Cu 2 The mass ratio of Se element in Se is 100:0.4, and then the mixture is dried at 85° C. in vacuum, and then calcined at 600° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0073] Comparative Example 3
[0074] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0075] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0076] 2) The sintered material obtained in step 1) and TiO 2 and ethylene glycol organic solvent are mixed evenly in a high energy ball mill to form a mixture, wherein the sintered material and TiO 2 The total mass concentration of the sintered material and TiO is 40%. 2 The mass ratio of the Ti element in the mixture is 100:0.4, and then the mixture is dried at 85° C. in a vacuum oven, and then calcined at 600° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0077] Comparative Example 4
[0078] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0079] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 The precursors are mixed uniformly according to the molar amount of each sodium element and the molar amount of the total nickel, iron and manganese elements in a ratio of 0.70:1, and the uniformly mixed materials are calcined at 930° C. at a heating rate of 2° C. / min in an air atmosphere in a box furnace for 10 hours, cooled and crushed to obtain a burnt material;
[0080] 2) The sintered material obtained in step 1) and Cu 2 Se metal selenium compound and ethylene glycol organic solvent are mixed in a high energy ball mill to form a mixture. 2 The total mass concentration of Se is 40%, the sintered material and Cu 2 The mass ratio of Se element in Se is 100:0.4, and then the mixture is dried at 85° C. in vacuum, and then calcined at 600° C. for 6 hours in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0081] Comparative Example 5
[0082] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0083] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 Precursor, TeO 3 The molar amount of each sodium element, the molar amount of the total element of nickel, iron and manganese, and the molar amount of the tellurium element are mixed uniformly in a ratio of 0.70:0.98:0.02, and the uniformly mixed materials are calcined at a temperature increase rate of 2°C / min to 930°C in an air atmosphere in a box furnace for 10 hours, and then cooled and crushed to obtain a burnt material;
[0084] 2) The sintered material obtained in step 1) and the ethylene glycol organic solvent are mixed uniformly in a high-energy ball mill to form a mixture, wherein the total mass concentration of the sintered material in the mixture is 40%, and then the mixture is dried at 85° C. in a vacuum, and then calcined at 600° C. for 6 h in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0085] Comparative Example 6
[0086] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0087] 1) Na 2 CO 3 、Ni 0.2 Fe 0.3 Mn 0.5 (OH) 2 The precursors are mixed uniformly according to the molar amount of each sodium element and the molar amount of the total nickel, iron and manganese elements in a ratio of 0.70:1, and the uniformly mixed materials are calcined at 930° C. at a heating rate of 2° C. / min in an air atmosphere in a box furnace for 10 hours, cooled and crushed to obtain a burnt material;
[0088] 2) The sintered material obtained in step 1) and the ethylene glycol organic solvent are mixed uniformly in a high-energy ball mill to form a mixture, wherein the total mass concentration of the sintered material in the mixture is 40%, and then the mixture is dried at 85° C. in a vacuum, and then calcined at 600° C. for 6 h in a nitrogen atmosphere, cooled, and sieved to obtain the sodium ion battery positive electrode material.
[0089] Test Example 1
[0090] The sodium ion battery positive electrode material in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the material appears as spherical particles formed by the accumulation of primary particle clusters, and the surface of the particles has a metal selenide coating.
[0091] Test Example 2
[0092] The sodium ion battery positive electrode materials in Examples 1-6 and Comparative Examples 1-6 were respectively used as sodium ion battery positive electrode materials to prepare button batteries. The preparation method was as follows: 95 (sodium ion battery positive electrode material): 2.5 (PVDF): 2.5 (SP) were uniformly mixed in N-methylpyrrolidone (solvent) to obtain positive electrode slurry, which was coated on aluminum foil, dried, and cut to form positive electrode sheets. The coating surface density of the positive electrode sheets was 12.0 mg / cm 2 , using metal Na sheet as the negative electrode and glass fiber as the separator, 1 mol / L NaPF 6 The ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio 1:1:0.5) solution was used as the electrolyte. During the test, the negative electrode sheet, electrolyte, separator, electrolyte, and positive electrode sheet were assembled into a CR2032 type button half-cell.
[0093] The newly prepared button half-cell was placed in the Blue Electric test system for rate performance test and cycle performance test. The specific test conditions are as follows:
[0094] Rate performance test: voltage range 2.0V-4.2V, rate performance test is carried out with 0.1C / 0.1C charge and discharge cycle 1 time, 0.2C / 0.2C charge and discharge cycle 1 time, 0.5C / 0.5C charge and discharge cycle 1 time, 1C / 1C charge and discharge cycle 1 time, 2C / 2C charge and discharge cycle 1 time, 4C / 4C charge and discharge cycle 1 time.
[0095] Cycle performance test: voltage range 2.0V-4.2V, first charge and discharge activation twice at 0.1C / 0.1C, then charge and discharge 50 times at 1C / 1C for cycle performance test.
[0096] The test results are shown in Table 1.
[0097] Table 1
[0098]
[0099]
[0100] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: 1) mixing a sodium source, a precursor and a hexavalent tellurium source, and performing a first calcination to obtain a sintered material; 2) The calcined material obtained in step 1), the metal selenium compound and the organic solvent are mixed, and subjected to a second calcination to obtain the sodium ion battery positive electrode material.
2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The second calcination in step 2) is carried out in an oxygen-containing atmosphere; Optionally, the second calcination is performed under an oxygen atmosphere.
3. The method for preparing the positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step 2), the second calcination is carried out under an inert gas atmosphere; Optionally, the second calcination is performed under a nitrogen atmosphere.
4. The method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 3, characterized in that: The precursor in step 1) includes a nickel-iron-manganese precursor; Optionally, the chemical formula of the nickel-iron-manganese precursor is Ni x Fe y Mn z (OH)2, and x+y+z=1, 0.1≤x≤0.8, 0.1≤y≤0.8, 0.1≤z≤0.8; The sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, and sodium oxalate; The hexavalent tellurium source is selected from tellurium trioxide.
5. The method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 4, characterized in that: In step 1), the ratio of the molar amount of the sodium element in the sodium source, the total molar amount of the metal elements in the precursor, and the molar amount of the tellurium element in the hexavalent tellurium source is 0.70:(0.95-0.99):(0.01-0.05); In step 1), the first calcination temperature is 900-1000° C. and the first calcination time is 10-24 hours; Optionally, in step 1), the first calcination atmosphere is an air atmosphere; Optionally, the first calcination further includes cooling and crushing steps.
6. The method for preparing the positive electrode material for sodium ion battery according to any one of claims 1 to 5, characterized in that: The metal selenium compound in step 2) is selected from at least one of NiSe, Cu2Se, CaSe, Fe2Se3, Co2Se3, Al2Se3, TiSe, SnSe2, and Sb2Se3: The organic solvent is selected from at least one of ethylene glycol, methanol, ethanol, isopropanol, ether, acetone and ethyl acetate.
7. The method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 6, characterized in that: The mass ratio of the sintered material to the selenium element in the metal selenium compound in step 2) is 100:(0.1-2.0); In the mixed solution formed by mixing the first sinter, the metal selenium compound and the organic solvent, the total mass concentration of the first sinter and the metal selenium compound is 20-50%; The sintered material, the metal selenium compound and the organic solvent are mixed by grinding.
8. The method for preparing the positive electrode material for sodium ion batteries according to any one of claims 1 to 7, characterized in that: In step 2), the second calcination temperature is 450-850° C., and the second calcination time is 5-10 h; Optionally, the second calcination further includes cooling and screening steps.
9. A sodium ion battery positive electrode material, characterized in that: The positive electrode material for a sodium ion battery is prepared by the method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material according to claim 9.
Citation Information
Cited By
Positive electrode material, preparation method thereof and lithium ion battery
CN116835673A